LITERATUR REVIEW: INTERVENSI NON FARMAKOLOGI TERHADAP PENURUNAN FREKUENSI MUAL DAN MUNTAH PADA IBU EMISIS GRAVIDARUM - Fatikhah Fatikhah (Jurnal Surya Muda, 2022)
Pregnancy causes physical, psychological and hormonal changes in the mother's body. One-third of women experiencing nausea and vomiting, this condition occurs because the influence of hormones affecting the increase in stomach acid. Pregnant women experience nausea, vomiting 2% in morning, 80% throughout the day and 18% continues until maternity, 1-2% experience hyperemesis gravidarum which has an impact on weight loss, dehydration, hemoconcentration (blood becomes thick) and ketonemia which has an impact on slowing blood circulation, which is oxygen and tissues. Emesis gravidarum also causes side effects on the fetus such as abortion, low birth weight, premature birth, and malforation in newborns, Intrauterine growth retardation (IUGR). Non-pharmacological interventions that can be used to avoid the risk of hyperemesis gravidarum, use ginger, lemon aroma therapy and acupressure. Exploratory research using literature review and design methods by taking sources from June to December 2021. Several journal portal websites used, Science Direct, Pub Med, proqueat, web of science Group and Google scolar .Based on keywords with the inclusion criteria of the journal year 20-17-2021, full text, related to the intervention of giving Ginger, Lemon Aromatherapy and acupressure. There were 747 articles, which giving ginger 473, aromatherapy lemon 240 and acupressure 34 based on the inclusion and exclusion criteria, there were 9 articles analyzed. The results of the study showed that the three interventions, which is Ginger, Lemon Aromatherapy and Acupressure, were very effective in reducing nausea and vomiting in Emissions gravidarum. the intervention of giving Ginger, Lemon Aromatherapy and Acupressure is very effective in reducing nausea and vomiting in mothers with gravidarum emission